PEMANFAATAN HIGHWAY SAFETY MANUAL (HSM) DI INDONESIA DALAM MEMPREDIKSI KECELAKAAN PADA SEGMEN JALAN - Iqbal, Muhamad; Tjahjono, Tri; Marino, Alan (Jurnal Transportasi, 2012)
The aims of this study were to investigate the variables affecting the highway safety function and to evaluate the prediction of frequency and accident fatality by using HSM method in several roadway segments in Indonesia. The studied road segments were toll road segments such as JakartaâCikampek, JakartaâBogorâCiawi (JAGORAWI), and JakartaâTanggerang toll road. The estimation of frequency and the fatality of accidents were developed from the prediction models, from which a combination of Safety Performance Functions (SPFs) and Empirical Baves method (EB). Based on the calculation, HSM method can be used to predicting accidents frequency in toll road segments with appropriate calibration factor (C) for each toll road or with consolidated calibration factor about 1,95. That value represents the accident rates on toll road segment in Indonesia is twice as big as America roadway segment.Keywords: HSM, SPFs, Calibration Factor, EB method, Toll Road